2000
DOI: 10.1002/1096-9861(20001225)428:4<609::aid-cne2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Domestication differentially affects cochlear nucleus subdivisions in the gerbil

Abstract: We analyzed the effects of domestication on the subdivisions of the cochlear nucleus in the gerbil (Meriones unguiculatus) by comparing their volumes and rostrocaudal extents in laboratory gerbils and in age-matched F1 offspring of gerbils caught in the wild. In addition, soma size was systematically analyzed in the anteroventral cochlear nucleus of both groups. Total cochlear nucleus volume and rostrocaudal extent were not significantly different between groups either for young (postnatal day 9) animals befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Since there are various physiological changes, the sensory systems could be affected, also. Anatomical data show, for example, that domestication differentially affects cochlear nucleus subdivisions in gerbils (Gleich et al, 2000). The primary aim of the present study was to evaluate possible effects of domestication on cochlear sensitivity and to assess if age-dependent deterioration of hearing as it is described for gerbils (e.g., Mills et al, 1990;Schmiedt et al, 1990;Tarnowski et al, 1991;Boettcher et al, 1993Boettcher et al, , 1996Sinnott et al, 1997;Hamann et al, 2002) or mice (Jacobson et al, 2003;Guimaraes et al, 2004) differs between domesticated and wild-type gerbils.…”
Section: Introductionmentioning
confidence: 87%
“…Since there are various physiological changes, the sensory systems could be affected, also. Anatomical data show, for example, that domestication differentially affects cochlear nucleus subdivisions in gerbils (Gleich et al, 2000). The primary aim of the present study was to evaluate possible effects of domestication on cochlear sensitivity and to assess if age-dependent deterioration of hearing as it is described for gerbils (e.g., Mills et al, 1990;Schmiedt et al, 1990;Tarnowski et al, 1991;Boettcher et al, 1993Boettcher et al, , 1996Sinnott et al, 1997;Hamann et al, 2002) or mice (Jacobson et al, 2003;Guimaraes et al, 2004) differs between domesticated and wild-type gerbils.…”
Section: Introductionmentioning
confidence: 87%
“…Initially, the data from RB and SC gerbils were analyzed separately because differences with respect to the morphology of the cochlear nucleus (CN) and in psychophysical, performance had been reported when comparing laboratory gerbils bred in captivity for many generations with gerbils originating from animals recently collected in the wild (Sinnott et al 1997;McGinn and Faddis 1998;Gleich et al 2000). Thus, it is possible that gerbils from colonies being bred separately for decades differ from one another.…”
Section: General Aspectsmentioning
confidence: 99%
“…This is consistent with our earlier observation that RB and SC gerbils were not different with respect to their puretone thresholds (Hamann et al 2002). Despite the reported difference between laboratory and wildstem gerbils in CN morphology (McGinn and Faddis 1998;Gleich et al 2000) and the degree of age-dependent threshold elevation for the detection of vowels (Sinnott et al 1997), gap-detection thresholds from our young RB gerbils closely resembled those of young wild-stem gerbils (Wagner et al 2003). All 14 gap-detection thresholds determined at levels greater than 30 dB SL by Wagner et al (2003) in 6 young gerbils were below 4 ms.…”
Section: General Aspectsmentioning
confidence: 99%
“…Reduction is greater in the cerebellum as in the forebrain (Leybold 2000). A reduction was also observed in the dorsal part of the cochlear nucleus (CN), whereas the size of its anteroventral part increased (Gleich et al 2000 Mammal biodiversity and abundance determined by the SDM2002 expedition. The results on biodiversity obtained in 1995 and 2002 must be interpreted separately.…”
Section: Discussionmentioning
confidence: 99%
“…lower brain weight (Stuermer et al 1997), less genetic variability (Neumann et al 2001), higher testosterone concentration and increased rate in spermatogenesis (Blottner et al 2000) indicated domestication in LAB gerbil. Further studies on wild offspring investigated the size of different brain subdivisions (Gleich et al 2000, Leybold 2000 and provided a method to determine age classes through skull characteristics (Tittmann 2002).…”
Section: Introductionmentioning
confidence: 99%